(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Let G be a connected graph. A subset S of V(G) is a connected co-independent hop dominating set in G if the subgraph induced by S is connected and V(G) S is an independent set where for each v V(G) S, there exists a vertex u S such that d_G(u,v)=2. The smallest cardinality of such an S is called the connected co-independent hop domination number of G. This paper presents the characterizations of the connected co-independent hop dominating sets in the edge corona and complementary prism of graphs and determines the exact values of their corresponding connected co-independent hop domination number.